Yttria-stabilized zirconia aided electrochemical investigation on ferric ions in mixed molten calcium and sodium chlorides - Hu, Hongbo; Gao, Yunming; Lao, Yigui; Qin, Qingwei; Li, Guangqiang; Chen, George Z. (Springer Verlag, 2018)
Electrolytic reduction of dissolved iron oxide to metal iron in molten salts with an inert anode is an alternative short route for steelmaking without CO2 emissions. A novel and simple integrated yttria-stabilized zirconia (YSZ) cell was constructed from a YSZ tube with a closed end. The YSZ tube played multiple functions, including the container for the molten salts, the solid electrolyte membrane in the O2−|YSZ|Pt|O2 (air) reference electrode (RE), and the solid electrolyte membrane between the working and counter electrodes (WE and CE). Electrochemical behavior of ferric ions (Fe3+) that were formed by dissolution of 0.5 wt pct Fe2O3 in the molten CaCl2-NaCl eutectic mixture was investigated on a Pt WE at 1273 K by various electrochemical techniques including cyclic voltammetry, linear scan voltammetry, square wave voltammetry, chronopotentiometry, chronoamperometry, and potentiostatic electrolysis. Analysis of the mechanism of electrode reactions was further assisted by scanning electron microscopy, energy dispersive X-ray spectroscopy, and X-ray diffraction. Some electrochemical parameters were obtained, including the number of exchanged electrons and the diffusion coefficient of ferric ions in the mixed molten salts. The results from various electrochemical techniques are in good agreement with each other, and show that the electrochemical reduction of Fe3+ to Fe in the molten salt mixture could be a single three-electron transfer step and diffusion-controlled reaction that was also possibly reversible. This work may form the foundation for extraction of iron and alloys from molten salts and also provide a stable O2−|YSZ|Pt|O2 (air) RE with wide applicability for investigation on electrochemical properties of other electroactive metal oxides in molten salts.